ARAHAN FUNGSI PEMANFAATAN LAHAN DI KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Firman Hudanil Haaq; Parijo Parijo; Loduvicus Manditya Hari Christanto (Universitas Tanjungpura, 2019)
AbstractLand use is process system spasial planning for hold the reins land use. Sejangkung sub-district happen flood every years because deviation land use by regional spatial planning at Sejangkung sub-district. This research as a purpose analyze deviation land use directive fungtion land use. The research sample is xsisting land use map, regional spatial planning map, fall of rain map, slope map, soil map. Method this research is descrivtif kualitatif. Overlay land use map and regional spatial planning map method two matriks dimentional. Overlay fall or rain map, slope map, and soil map for directive fungtion land use map. Result this research is sub-district Sejangkung exsisting land use is housing land use, work land use,service land use and agricultural land use. Housing land use have 266,05 hectare, work land use have 16,01 hectare, service land use have 12,49 hectare and agricultural have 51887,14 hectare. Regional spatial planning map at Sejangkung is housing land use, agricultiral land and protection region.Housing land planning have 3350,08 hectare, agricultural land have 41870,1 hectare and 1523,12 hectare. Deviation land use have 10013,23 hectare and directive fungtion land use have 60855,91 hectare. Keywords:Deviation Land Use, Directive Fungtion Land Use, Regional Spatial Planning